Introduction of metal precursors by electrodeposition for the in situ growth of metal–organic framework membranes on porous metal substrates. Issue 5 (17th January 2017) - Zhou, Sheng; Wei, Yanying; Zhuang, Libin; Ding, Liang-Xin; Wang, Haihui
Abstract : An efficient and generalizable strategy assisted by electrodeposition was developed for the in situ growth of various MOF membranes. Abstract : We report here a facile and efficient electrodeposition method to modify inexpensive porous stainless-steel nets for use as substrates in the in situ growth of metal–organic framework membranes, such as ZIF-8, ZIF-67 and HKUST-1. Using this method, different metal precursors can be electrodeposited depending on the central metals required in the target metal–organic frameworks. The inorganic modifiers prepared by this approach are sufficiently reactive for the one-step growth of continuous metal–organic framework membranes; their reactivity is comparable with that of organic functional groups. The procedure is also green and cost-effective, which is promising for use in large-scale production.